Microwave assisted preparation of onion skin activated carbon: Application for removal of tetracycline - Ait Ouaissa, Y; Djbrouni, A; Chabani, S; Chabani, M; Amrane, A; Bensmaili, A (جامعة الوادي - university of el oued, 2021)
The activated carbon prepared from onion skin by H2SO4 activation under microwave radiation was investigated. The effect of different condition in order to obtain the high removal efficiency of Tetracycline and carbon yield was studied. The optimum condition has been identified at the acid concentration of 1N, Microwave power of 720W, microwave radiation of 5min and impregnation heating time of 48 h. The obtained activated carbon under these conditions was characterized by scanning electron microscopy and by FTIR spectra. Microwave energy is predicted to be for fuel technology in various areas, while its progress represents an expanding field in the area of adsorption science.
Article
Keywords: Adsorption; Activated carbon; Tetracycline; Microwave